The loss of the soul and the myth of the living dead. A Jungian approach to a mental health problem in a public hospital in Buenos Aires - González‐Casal, Cristina (Journal of analytical psychology, 2022)
This study is about the intervention carried out by a group of professionals from the Interdisciplinary Mental Health Team of the Emergencies Department in a public hospital in Buenos Aires City between 2017 and 2019. It arose from the need to respond to a public health problem related to the increasing number of patients living in situations involving homelessness, drug abuse, violent behaviour and criminal background. The multiple facets of this problem made us think about the impossibility of addressing it only in the individual sense of each patient. We were forced to admit that we were facing a problem of a complex, collective, social and institutional order, which the predominant medical model had neither been able to handle nor understand. We sought to include a Jungian approach to this contemporary problem found in large Latin American cities. Amplifying a symbolic base allowed us to understand creatively the complexity of the phenomenon, which could not be read in any manner other than the social and collective. Cette étude porte sur l’intervention menée dans un hôpital public de Buenos Aires entre 2017 et 2019 par un groupe de professionnels de l’équipe interdisciplinaire de Santé Psychique. Elle fut mise en place du fait du besoin de répondre au problème de santé publique lié au nombre croissant de patients vivant sans domicile fixe, avec des problèmes de drogue, de comportement violent et de criminalité. Les aspects multiples de ce problème nous amenèrent à penser qu’il était impossible d’y faire face seulement sur la base de chaque patient en tant qu’individu. Nous avons été forcés d’admettre que nous étions confrontés à un problème complexe, collectif, d’ordre social et institutionnel, que le modèle médical prédominant n’avait pu ni résoudre ni comprendre. Nous avons cherché à inclure une approche Jungienne à ce problème contemporain que l’on retrouve dans les grandes villes d’Amérique Latine. L’amplification d’un fondement symbolique nous a permis de comprendre de manière créative la complexité du phénomène, dont la lecture ne pouvait qu’être sociale et collective. Diese Studie befaßt sich mit der Intervention, die von einer Gruppe von Fachleuten des interdisziplinären Teams für psychische Gesundheit bei der Notfallabteilung eines öffentlichen Krankenhauses in der Stadt Buenos Aires zwischen 2017 und 2019 durchgeführt wurde. Es entstand aus der Notwendigkeit, auf ein Problem der öffentlichen Gesundheit im Zusammenhang mit der steigenden Zahl von Patienten zu reagieren, die in Situationen wie Obdachlosigkeit, Drogenmißbrauch, gewalttätigem Verhalten und kriminellem Hintergrund leben. Die vielen Facetten dieses Problems ließen uns über die Unmöglichkeit nachdenken, es nur im individuellen Sinne jedes Patienten anzugehen. Wir mußten zugeben, daß wir vor einem Problem komplexer, kollektiver, sozialer und institutioneller Ordnung standen, das das vorherrschende medizinische Modell weder bewältigen noch verstehen konnte. Wir versuchten, einen Jungianischen Ansatz für dieses zeitgenössische Problem, das man in großen lateinamerikanischen Städten findet, einzubeziehen. Die Amplifikation einer symbolischen Basis ermöglichte es uns, die Komplexität des Phänomens kreativ zu verstehen, die auf keine andere Weise als sozial und kollektiv gelesen werden konnte. Questo studio riguarda l’intervento effettuato da un gruppo di professionisti del Team Interdisciplinare di Salute Mentale del Pronto Soccorso in un ospedale pubblico nella città di Buenos Aires tra il 2017 e il 2019. È nato dalla necessità di rispondere ad un problema di salute pubblica legato al crescente numero di pazienti che includeva coloro che vivevano senza fissa dimora, o facevano abuso di droghe, o mostravano comportamenti violenti e precedenti penali. Le molteplici sfaccettature di questo problema ci hanno fatto pensare all’impossibilità di affrontarlo solo nel senso individuale di ciascun paziente. Siamo stati costretti ad ammettere che ci trovavamo di fronte ad un problema di ordine complesso, collettivo, sociale ed istituzionale, che il modello medico predominante non era stato in grado né di gestire né di comprendere. Abbiamo cercato di includere un approccio junghiano a questo problema contemporaneo riscontrato nelle grandi città latinoamericane. L’amplificazione di una base simbolica ci ha permesso di comprendere creativamente la complessità del fenomeno, che non poteva essere letto in altro modo se non in quello sociale e collettivo. Это исследование посвящено интервенции, проведенной группой профессионалов из Междисциплинарной комнады психического здоровья Департамента по чрезвычайным ситуациям в государственной больнице в Буэнос‐Айресе в период с 2017 по 2019 год. Идея возникла из необходимости среагировать на проблему общественного здравоохранения, связанную с ростом числа пациентов, живущих в условиях бездомности, злоупотребления наркотиками, агрессивного поведения и криминального прошлого. Многогранность этой проблемы заставила задуматься о невозможности решить ее только в индивидуальном ключе. Мы были вынуждены признать, что столкнулись с вопросом сложного, коллективного, социального и институционального порядка, с которым преобладающая медицинская модель не могла ни справиться, ни понять. Мы стремились включить юнгианский подход к этой современной проблеме, характерной для крупных латиноамериканских городов. Усиление символической базы позволило нам творчески осознать сложность явления, которое нельзя было интерпретировать никаким другим способом, кроме социального и коллективного. Este trabajo trata sobre una intervención realizada por un grupo de profesionales del Equipo Interdisciplinario de Salud Mental del Departamento de Emergencias de un Hospital Público de la Ciudad de Buenos Aires entre 2017‐2019. Surgió ante la necesidad de dar respuesta a una problemática de Salud Pública relacionada con el incremento de pacientes que viven en situación de calle con consumo de drogas, conductas violentas y antecedentes delictivos. Las múltiples facetas de este problema nos llevó a reflexionar sobre la imposibilidad de darle solución si solamente lo enfocábamos desde lo individual de cada paciente. Tuvimos que admitir que nos encontrábamos ante un problema complejo, de orden colectivo, social e institucional que el modelo médico predominante era incapaz de comprender o resolver. Entonces pensamos observar desde un enfoque Junguiano este problema contemporáneo que encontramos en las grandes urbes de América Latina. Amplificar una base simbólica nos posibilitó comprender creativamente la complejidad del fenómeno, que no podía ser abordado sino desde lo social y colectivo. 活死人中灵魂和神话的丧失。在布宜诺斯艾利斯公立医院中对心理健康问题的荣格取向治疗 这篇论文研究了自2017年至2019年间, 在布宜诺斯艾利斯市的公立医院的急诊部门中, 一个跨学科心理健康专业团队所进行的干预工作。这提示我们需要对一些公众健康问题作出回应, 这些健康问题关系着越发增多的一些病人, 他们处于流离失所、药物滥用、暴力行为和犯罪的背景之中。这一问题的多个面向让我们去思考, 我们无法只是从一个孤立案例的角度去呈现这个问题。我们被迫着去承认, 我们正面临一个复杂的、集体性的、社会和机构秩序性的问题, 而占主导地位的医疗模式对这些问题既不能应对也不能理解。我们尝试把荣格取向引入这个拉美城市广泛存在的现代问题的解决上。在象征基础上的放大让我们可以用创造性的方式理解这个复杂的现象, 这一现象除了从社会和集体的层面去理解, 再无其它的方式。 Este estudo trata da intervenção realizada por um grupo de profissionais da Equipe Interdisciplinar de Saúde Mental do Departamento de Emergências em um hospital público na Cidade de Buenos Aires entre 2017 e 2019. Surgiu da necessidade de responder a um problema de saúde pública relacionado ao número crescente de pacientes que vivem em situações envolvendo situação de rua, abuso de drogas, comportamento violento e antecedentes criminais. As múltiplas facetas desse problema nos fizeram pensar na impossibilidade de abordá‐lo apenas no sentido individual de cada paciente. Fomos forçados a admitir que estávamos diante de um problema de ordem complexa, coletiva, social e institucional, que o modelo médico predominante não era capaz de lidar nem entender. Procuramos incluir uma abordagem junguiana para esse problema contemporâneo encontrado nas grandes cidades latino‐americanas. Ampliar uma base simbólica nos permitiu entender criativamente a complexidade do fenômeno, que não poderia ser lido de outra maneira além do social e coletivo.